EFFECT OF RICE HUSK RESIDUE ON MAIZE IN MINNA, NIGERIA - EZE, P. C.*, MUSA, J. J., ONYEKWERE, I. N and BALOGUN, I. A. (The Journal of Research ANGRAU, 2020)
The experiment was conducted during the 2014 and 2015 cropping seasons to study the effectof the method (surface application and incorporation)and rate of application(0, 10 and 15 tons ha-1)of rice husk-residue on maize plant height and yield indices. Incorporation of rice husk-residue at 15tons ha-1 produced the tallest (P 0.05) maize plants and longest maize cobs, but method of applicationof rice husk-residue had no significant effect on grain yield, stover yield and cob weight. Residueincorporation produced longer cobs than surface application. However, 15 tons ha-1 residue applicationrate resulted in the highest (P 0.05) grain yield, cob length and cob weight. The study suggests thatincorporation of rice husk-residue rather than surface application as mulch, at 15 tons ha-1 will ensurebetter maize performance in Minna, Nigeria.